Genomic repertoire of the Woeseiaceae/JTB255, cosmopolitan and abundant core members of microbial communities in marine sediments - Mußmann, Marc; Pjevac, Petra; Krüger, Karen; Dyksma, Stefan (The ISME Journal, 2017)
To date, very little is known about the bacterial core community of marine sediments. Here we study the environmental distribution, abundance and ecogenomics of the gammaproteobacterial Woeseiaceae /JTB255 marine benthic group. A meta-analysis of published work shows that the Woeseiaceae /JTB255 are ubiquitous and consistently rank among the most abundant 16S rRNA gene sequences in diverse marine sediments. They account for up to 22% of bacterial amplicons and 6% of total cell counts in European and Australian coastal sediments. The analysis of a single-cell genome, metagenomic bins and the genome of the next cultured relative Woeseia oceani indicated a broad physiological range, including heterotrophy and facultative autotrophy. All tested (meta)genomes encode a truncated denitrification pathway to nitrous oxide. The broad range of energy-yielding metabolisms possibly explains the ubiquity and high abundance of Woeseiaceae /JTB255 in marine sediments, where they carry out diverse, but yet unknown ecological functions.